The American West : a new interpretive history - Hine, Robert V., 1921-2015; Faragher, John Mack, 1945- (Yale University Press, 2000)
This survey of frontier history traces the story from the first Columbian contacts between Indians and Europeans to the multicultural encounters of the modern world.